Gastrointestinal thiaminase vs. ration changes - Soita, H.W.; Brent, B.E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
High levels of the thiamin-destroying enzyme, thiaminase I, were found in the feces of 3 of 50 apparently healthy dairy cows. All high fecal thiaminase I levels returned to normal within 3 weeks, indicating that thiaminase I occurs in "spikes" rather than continuing at elevated levels. All cows sampled had some thiaminase I, but the upper end of the "normal" range in feces was about 3.5 μmol/min/l. Thiaminase I levels were higher in the first than in subsequent lactations. When spikes in thiaminase I activity occurred, they were concentrated within about 20 days of calving and of the associated change to a high concentrate diet. Lactating cows fed a high concentrate post-calving diet had more thiaminase I than prepartum cows fed a lower energy diet.
Keywords: Beef; Polioencephalomalacia; Thiamin; Thiaminase